Servant Leadership Style dan Komunikasi Interpersonal Terhadap Motivasi Kerja Pegawai Bank Nagari Cabang Siteba - Gilang Pratama Putra; Aminar Sutra Dewi (Journal of Management and Creative Business, 2024)
A person's motivation is what drives them to work in such a way as to achieve their desired level of self-satisfaction. Many people believe that fair and good imbalances can inspire them to work well, but in reality, their performance may not be at its best even though they receive proper rewards. The two main factors that can determine the success of a company are supporting infrastructure and motivation. The results of this research are that Servant Leadership has a large influence on Work Motivation, so that the first hypothesis is accepted. The influence of interpersonal communication on work motivation is quite large, thus strengthening the acceptance of the second hypothesis.